Exploration of Reinforcement Learning Methods when Training a Dice Game Playing Agent - Klejda Alushi (2024)
This thesis will use different reinforcement learning algorithms to train a neural network to play a dice game. It will analyse how these algorithms are influenced by stochastic processes and by the dimensions of the neural network.
Keywords: Artificial Intelligence; Deep Learning; Reinforcement Learning; Dice Game; Advantage Actor Critic